Use of videos to support teaching and learning of clinical skills in nursing education: A review. (July 2016) - Forbes, Helen; Oprescu, Florin I.; Downer, Terri; Phillips, Nicole M.; McTier, Lauren; Lord, Bill; Barr, Nigel; Alla, Kristel; Bright, Peter; Dayton, Jeanne; Simbag, Vilma; Visser, Irene
Abstract: Information and communications technology is influencing the delivery of education in tertiary institutions. In particular, the increased use of videos for teaching and learning clinical skills in nursing may be a promising direction to pursue, yet we need to better document the current research in this area of inquiry. The aim of this paper was to explore and document the current areas of research into the use of videos to support teaching and learning of clinical skills in nursing education. The four main areas of current and future research are effectiveness, efficiency, usage, and quality of videos as teaching and learning materials. While there is a clear need for additional research in the area, the use of videos seems to be a promising, relevant, and increasingly used instructional strategy that could enhance the quality of clinical skills education. Highlights: Students value ICT-based solutions to support the learning of clinical nursing skills. Blended learning incorporating video could enhance acquisition of knowledge and skills. Current areas of research in clinical education using videos is focused on effectiveness, efficiency, usage and quality